Pengaruh Model Pembelajaran Example Non Example Terhadap Keterampilan Menulis Teks Persuasi Siswa Kelas VIII SMP Deli Murni Sukamaju - Cyntia Putri Hutagalung; Salmah Naelofaria (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The aim of this study was to identify the effect of the example non example learning model on the persuasive text writing skills of Grade VIII students of SMP Deli Murni Sukamaju. The learning model used is example non example, where students analyze examples in the form of pictures, photos, and cases that contain problems. This study uses pictures and cases as examples in the example non example learning model. The population of this study were all students of class VIII SMP Deli Murni Sukamaju, with a sample of 29 students from class VIII-1. The method used in this study was an experimental design with one group pre-test and post-test. Data analysis techniques include hypothesis testing, normality testing, and analysis requirements testing. The pretest results show an average score of 62.10 in the less category. However, the posttest results showed an average score of 86.83 when using pictures and 87.86 when using cases. The results of hypothesis testing using the "t" test show a value of 12.12 > 2.048 when using pictures and 11.92 > 2.048 when using cases. Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant effect of using the example non example learning model with cases on the persuasive text writing skills of class VIII students of SMP Deli Murni Sukamaju.